COMMUNITY PARTICIPATION IN DEVELOPING FACILITIES AND INFRASTRUCTURE STANDARDS IN ISLAMIC ELEMENTARY SCHOOL OF KEEROM-PAPUA - Umkabu, Talabuddin; Ramah, Bahaking; Muzakkir, Muzakkir; Azisah, St. (Jurnal Diskursus Islam, 2020)
This paper describes community participation in the development of standard facilities and infrastructure for Islamic Elementary School of Keerom-Papua. This type is qualitative research, the research approach is a phenomenological perspective and a descriptive analysis approach, data sources are primary data and secondary data, data collection techniques through observation, interviews, and documentation, research instruments namely, researchers as key instruments, observation guides, interview guides and reference documentation, processing techniques and data analysis, namely data reduction, data presentation, conclusion and verification, data validity testing, namely triangulation techniques, checking the correctness of information, discussing and consulting data, and extending the research time. The results showed community participation in the development of standard facilities and infrastructure at Islamic Elementary School of Keerom-Papua concluded that the community was enthusiastic about participating in building mushallah/mosque and procuring canteens and greenhouses. Boarding and equalizing the madrasah yard, fencing the front door of the madrasah, making madrasah fish pond gardens, and the land used as the location for the construction of madrasah and mosques are the provision of traditional leaders (non-Muslims) and the procurement of sports equipment, while the procurement of the main facilities, specifically for Islamic Elementary School The private sector shows that there is participation but it is not maximal while public Islamic Elementary School have not seen maximum community participation, it is due to a lack of public awareness of a sense of responsibility in developing madrasah, and building communication to exchange opinions with the community about the importance of community participation in developing madrasah as a charity Jariyah and social activities.